RNA silencing in Drosophila. - Kavi, H.H.; Fernandez, H.R.; Xie, W.; Birchler, J.A. (FEBS Letters, 2005)
Knowledge of the role of RNA in affecting gene expression has expanded in the past several years. Small RNAs serve as homology guides to target messenger RNAs for destruction at the post-transcriptional level in the experimental technique known as RNA interference and in the silencing of some transgenes. These small RNAs are also involved in sequence-specific targeting of chromatin modifications for transcriptional silencing of transgenes, transposable elements, heterochromatin and some cases of Polycomb-mediated gene silencing. RNA silencing processes in Drosophila are described.